Survival Outcomes and Prognostic Analysis Following Greater Cytoreductive Radiotherapy in Patients With Metastatic Prostate Cancer - Zhang, Zitong; Wei, Min; Mai, Lixin; Li, Yonghong; Wu, Jianhua; Huang, Hong; Huang, Sijuan; Lin, Maosheng; Jiang, Xiaobo; Zhou, Fangjian; Liu, Mengzhong; Liu, Yang; et al. (Frontiers in Oncology, 2020)
Purpose: To assess the survival outcomes of patients with metastatic prostate cancer (mPCa) who undergo greater cytoreductive radiotherapy in a real-world clinical practice and determine their prognostic factors. Methods: We performed a retrospective study of 160 patients with mPCa who underwent cytoreductive radiotherapy between 2009 and 2018 at a single institution. The degree of the cytoreductive burden was calculated for each patient. Overall survival (OS) was calculated from the date of detection of metastases. Variables associated with prostate-specific antigen (PSA) response and OS were evaluated via univariate and multivariate analyses. Results: The median follow-up period was 47.2 months. The median OS was 42.3 months with a 5-year OS rate of 37.9%. The PSA levels of 90 patients (56.7%) decline by >50% after radiotherapy. The 5-year OS rates of patients who underwent total, major, and minor cytoreductive radiotherapy were 53.4%, 38.2%, 17.6%, respectively; the corresponding median OS intervals were 62.5, 41.0, and 24.4 months, respectively (P<0.001). A greater extent of cytoreduction (P<0.05), lower PSA at radiotherapy initiation (hazard ratio 0.51, 95% confidence interval [CI] 0.33–0.78; P=0.002) and better PSA response (hazard ratio 0.47, 95% CI 0.30–0.72; P<0.001) were independent factors associated with superior OS. A high metastatic burden (as defined in the CHAARTED trial) was the only independent predictor of a poorer PSA response (odds ratio 0.36, 95% CI 0.19-0.69; P=0.002). Grade 2 late gastrointestinal and genitourinary toxicities were observed in 3 and 2 patients, respectively, and only 1 patient had grade 3 late gastrointestinal toxicity. Conclusion: Cytoreductive radiotherapy is effective and safe in select patients with mPCa. Greater cytoreduction, together with lower PSA at radiotherapy initiation and improved PSA response are favourable prognostic factors. Further studies are needed to confirm our findings.